2013
DOI: 10.1039/c3cp52384e
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale electronic transport in Li1+xNi1/3−uCo1/3−vMn1/3−wO2: a broadband dielectric study from 40 Hz to 10 GHz

Abstract: This work is the first detailed study concerning the multiscale electronic transport and its temperature dependence in the LiNi1/3Co1/3Mn1/3O2 (NMC) family, high-capacity electrode materials for lithium ion batteries. Powders with two different mean cluster sizes (3 μm and 10 μm) but the same particle sizes (0.4 to 1.3 μm) were measured. The detailed formula of the studied compound is Li1.04Ni(2+)0.235Ni(3+)0.09Mn(4+)0.315Co(3+)0.32O2. Different electrical relaxations are evidenced, resulting from the polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 36 publications
1
36
0
2
Order By: Relevance
“…With respect to electronic conductivity, we know of no published measurements for NMC 333 and NMC 523 compositions. Seid et al 22 reported that the electronic conductivity of Li 1 Thus our objective in this work is to systematically characterize and interpret the transport properties of NMC 333 and NMC 523 . We use additive-free, single phase sintered samples in which the extrinsic effects due to binders, conductive additives, and particle microstructures that may be present in composite electrodes are avoided.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to electronic conductivity, we know of no published measurements for NMC 333 and NMC 523 compositions. Seid et al 22 reported that the electronic conductivity of Li 1 Thus our objective in this work is to systematically characterize and interpret the transport properties of NMC 333 and NMC 523 . We use additive-free, single phase sintered samples in which the extrinsic effects due to binders, conductive additives, and particle microstructures that may be present in composite electrodes are avoided.…”
mentioning
confidence: 99%
“…However, there is surprisingly little, and conflicting, data on the basic transport properties of the NMC family of compounds. [19][20][21][22][23] Wu et al, 19 and Hao 20 measured using the GITT technique the chemical diffusivity of NMC 333 based composite electrodes (e.g., NMC powder combined with polymer binder and carbon additive) as a function of lithium content, and reported results differing by two orders of magnitude from each other. Furthermore, whereas Hao 20 reported that the chemical diffusivity of NMC 333 is nearly independent of lithium content, Wu et al 19 found two orders of magnitude variation of lithium diffusivity with lithium content.…”
mentioning
confidence: 99%
“…While , Seid et al have demonstrated that within NCM material, the clusters of particles bring boundaries, junctions and interfaces. [10,11] This will result in various polarizations ranging from interatomic distances to macroscopic sizes, leading to the conductivity is different in multiscale. The multiscale conductivities should be taken in account when exploring the intrinsic kinetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, high temperature processing may have induced a change in the properties of the grain boundaries. For example, the formation of an insulating amorphous film on interparticle boundaries has been observed in previous studies on calcined powder clusters, resulting in significant decreases to the electrical conductivity between grains . These changes to the grain boundary properties would also be reflected in the mechanical performance.…”
Section: Resultsmentioning
confidence: 76%